Responses of blood hormones to the maximal rowing ergometer test in college rowers - Jurimae, J.; Jurimae, T. (The Journal of Sports Medicine and Physical Fitness, 2001)
BACKGROUND: The purposes of this study were to investigate the resting levels and the acute hormonal response of total testosterone (Ttot), free testosterone (Tfree), cortisol (C) and Tfree:C ratio to the 6-minute all-out rowing ergometer test. METHODS: Experimental design: cross-sectional study to investigate the responses of blood hormones to the maximal rowing ergometer test in college rowers. Participants: eight college level male rowers (22.0+/-2.8 yrs, 191.8+/-4.1 cm, 85.4+/-4.3 kg, BMI: 23.2+/-1.3 kg.m-2) took part in this investigation. Interventions: a graded exercise test at the intensities of 150, 200 and 250 W (6-minute each) and a 6-minute all-out test on a rowing ergometer (Concept II, Morrisville, USA) were performed at separate measurement sessions. Measures: heart rate (HR) was recorded at the end of each load during a graded exercise test. Individual physical working capacity of rowers was calculated at the maximum HR recorded during a 6-minute all-out test. Venous blood samples were obtained 3 minutes before and immediately after the 6-minute all-out test to determine the concentration of Ttot, Tfree, Tfree:C ratio, glucose and lactate (LA) in blood. RESULTS: Mean power was 354.3+/-26.8 W and HR 190.9+/-5.1 beats.min-1 during the all-out test. Mean blood LA concentration at the end of the all-out test was 13.46+/-1.44 mmol.l-1. The all-out test on the rowing ergometer did not change significantly the concentration of Ttot (before: 17.54+/-4.34; after: 20.03+/-4.80 nmol.l-1), Tfree (before: 0.423+/-0.111; after: 0.436+/-0.112), C (before: 477.50+/-119.34; after: 477.63+/-132.51 nmol.l-1) and Tfree:C ratio (before: 0.922+/-0.282; after: 0.973+/-0.320 yen10-3). The transformation of these hormone values to effect sizes (ES) demonstrated that all-out test only moderately (ES<0.61) influenced these hormone levels. Significant relationships were observed between the resting levels of Ttot and Tfree, and mean power of the 6-minute all-out test (r=0.65 and r=0.86, respectively). There was a non-significant increase in the level of Ttot following the all-out rowing ergometer test which was significantly related to mean power (r=0.73) and covered distance (r=0.67). CONCLUSIONS: The results suggest that there are no significant changes in hormone levels during a 6-minute all-out rowing ergometer test. However, rowing performance is positively related to the resting values of Ttot and Tfree, and the non-significant changes in Ttot level following a 6-minute all-out test.